Principles for integrated environmental management of military training areas. (April 2017) - Zentelis, Rick; Lindenmayer, David; Roberts, J. Dale; Dovers, Stephen
Abstract: Military Training Areas (MTAs) cover an estimated 200–250 million hectares globally, occur in all major ecosystems, and are potentially significant conservation assets. In some jurisdictions, MTAs may be the largest terrestrial land use category that is owned and operated by a sovereign government. Despite this, MTAs are not recognised as either a conservation or environment protection resource. Further, no MTAs are managed for their environmental values, defined as aspects of the environment that are valued by society, nor is there any specific MTA management guidance that details how both the military training and environmental values of a MTA can be maintained. We conducted a desktop review of Australian and German MTA management documentation to determine whether they contained management principles that recognised both military training and environmental values. Management documentation from these two countries was chosen as they are considered to be among countries at the forefront of MTA management globally. Our review determined that both the Australian and German management regimes do not have specific management principles for these values. This is likely to be the case for the majority of MTAs globally. For the first time, we develop MTA management principles that integrate the management of both military training objectives and environmental values. Key to achieving this integration is an understanding of the intersection of the impacts of military training on the environment, and the known, or potential, environmental values of a particular training area. To assist with the implementation of the management principles, we developed a new conceptual framework for the management of MTAs. The framework contains two adaptive management loops. The first focuses on the management of environmental values of MTAs, the second targets the military training values of MTAs. These two management loops facilitate for the development of management practices that optimise MTA management for both military training and biodiversity conservation.